The mediating role of parasocial interaction in the relationship between loneliness and netflix binge-watching tendencies: a case study of Malaysian university students during the COVID-19 pandemic - Tengku Siti Aisha Tengku Mohd Azzman Shariffadeen,; Aini Maznina A. Manaf,; Tak, Jie Chan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Streaming services such as Netflix are already penetrating the mainstream market in Malaysia. Netflix offers a wide range of binge-worthy content to young adults, such as K-dramas, anime, thrillers, rom-coms, sitcoms, or reality television shows. As a newer form of media engagement, media researchers are just beginning to understand the meaning of binge-watching, and how motivation to binge-watch (MBW) predicts binge-watching tendencies (BWT). Research on parasocial relationships formed with Netflix characters and how they influence BWT is also relatively scarce. Thus, we seek to identify predictors of BWT from the uses and gratification (U&G) perspective. We predict that parasocial interaction (PSI) will mediate the relationship between loneliness and binge-watching tendencies (BWT). Six hypotheses were tested using zero-order correlations and PROCESS Macro Hayes. A cross-sectional online survey was constructed using Google Forms, and distributed among university students in Malaysia during the COVID-19 pandemic (N = 284). Data was collected from October to December 2021. Four hypotheses were supported; results indicate that PSI, stress relief, and enjoyment predicted BWT. PSI also mediated the relationship between loneliness and BWT. Thus, parasocial relationships formed with Netflix characters prompted lonelier individuals to binge-watch more. The repercussions of these findings on U&G, PSI, and binge-watching literature will be discussed.